A simple finding on variable amplitude (Gassner) fatigue SN curves obtained using Miner's rule for unnotched or notched specimen. (1st May 2017) - Ciavarella, M.; D'Antuono, P.; Demelio, G.P.
Highlights: We obtain Gassner curves using the simple Palmgren-Miner's law and Point Critical Distance Method. We find (either analytically or numerically) Gassner curve are simply shifted CA curves. Spectrum loading results in the same multiplicative term for notched, racked and unnotched specimen. Experimental data from the Literature seem to confirm these simple findings, despite the strong assumptions. The iterative solution suggested by Susmel and Taylor seems not needed. Abstract: In this note, starting from the SN curve under Constant Amplitude (CA) for the fatigue life of the uncracked (plain) specimen, we obtain that Gassner curves for Variable Amplitude (VA) loading using the simple Palmgren-Miner's law are simply shifted CA curves. Further, using the Critical Distance Method in a very clean and powerful form proposed by Susmel and Taylor for VA loading, we find similar result for notched specimen, the spectrum loading results in the same multiplicative term for notched, cracked and unnotched specimen. Hence, the present proposal can be considered as a simple empirical unified approach for rapid assessment of the notch effect under random loading, which simplifies the recent proposal by Susmel and Taylor. To their extensive validations, we add some specific comparison with experimental data from the Literature on our further findings.